Answer: 6
Step-by-step explanation:
1/2 = 3/6
2/3 = 4/6
First we use sin(a+b)= sinacosb+sinbcosa
and cos(a+b)=cosa cosb -sinasinb
tan(x+pi/2)= sin(x+pi/2) / cos(x+pi/2)
and sin(x+pi/2) = sinxcospi/2 + sinpi/2cosx =cosx,
<span>cos(x+pi/2) = cosxcospi/2- sinxsinpi/2= - sinx,
</span> because <span>cospi/2 =0, </span>and <span>sinpi/2=1
</span><span>=tan(x+pi/2)= sin(x+pi/2) / cos(x+pi/2)= cosx / -sinx = -1/tanx = -cotx
</span>from where <span>tan(x+pi/2)=-cotx</span>
Answer:
Answers are below
Step-by-step explanation:
3 - 7 = -4
4 - 6 = -2
3 + -6 = -3
4 - - 1 = 5
-5 + -5 = -10
-3 + 5 = 2
-4 -6 = -10
Hope this helps!!
R=23 because its slope the formula is Y-Y/X-X
Answer:
i think its neither
Step-by-step explanation: